The role of community-based democracy volunteers in increasing the voter participation in general elections - Mohammad Nur Huda; Suharno Suharno (Masyarakat, Kebudayaan dan Politik, 2023)
Voter participation in general elections is one of the challenges for general election organizers. Various attempts were made to increase voter participation in every general election. This study aims to identify the role of community-based democracy volunteers in increasing the voter participation, analyzing the increase in voter participation, and analyzing the obstacles that affect the implementation of communitybased democracy volunteer activities in 2019 in Pekalongan City. This research is a descriptive study with a qualitative approach case study toward The General Elections Commission of Pekalongan City. The results suggested that the role of community-based democracy volunteers in increasing voter participation was manifested through the socialization of elections to the community, considering the large number of communities in Pekalongan and the members who were also voters in the 2019 election. The socialization carried out by community-based democracy volunteers in Pekalongan greatly influenced the increase in voter turnout in the 2019 elections which reached 84%. The obstacles occurred during socialization by community-based democracy volunteers could be properly resolved. Community-based democracy volunteers have a very important role in increasing voter participation in elections through socialization activities carried out.